The Role of Cobalt Exposure in the Incidence of Cancer: A Systematic Review and Meta-Analysis Protocol - Halimi, Aram; Karimiyan, Mobina; Khavari, Tina; Azizi, Fatemeh; Asadipour, Fatameh; Soleimani, Yaser; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Environment and Cancer, 2023)
Background: Cobalt, a versatile transition metal, has widespread industrial applications, but its potential link to cancer has raised concerns. This systematic review and meta-analysis protocol aims to investigate the relationship between cobalt exposure and cancer incidence, addressing its implications for public health and occupational safety. Methods: A comprehensive literature search will be conducted in PubMed, Scopus, and Web of Science databases up to August 2023. Eligible studies will include human participants exposed to cobalt, with cancer incidence as an outcome. Both observational and analytical study designs will be considered. Results: Quantitative meta-analysis will be performed using random-effects models to calculate pooled Incidence Rate Ratios (IRRs). Subgroup and sensitivity analyses will explore heterogeneity and potential bias. Findings will be compared with prior research to assess consistency and support. Conclusion: This systematic review and meta-analysis protocol aims to provide a comprehensive assessment of the potential association between cobalt exposure and cancer incidence. The outcomes could have significant implications for occupational health, public safety, and policy decisions.